2004
DOI: 10.1530/eje.0.1500743
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of intraoperative fluorescence diagnosis of parathyroid glands

Abstract: Objective: Identification of parathyroid glands is often a challenge even for experienced surgeons. The feasibility and efficacy of fluorescence diagnosis for localization of parathyroids has already been proven in an experimental setting. In preparation for a clinical application of this technique in patients undergoing surgery for hyperparathyroidism, we evaluated the kinetics of fluorescence diagnosis. Design and methods: Fifty rats were randomized into eight groups with different photosensitization paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
9
1
Order By: Relevance
“…Fluorescence diagnosis using aminolevulinic acid (ALA) to identify parathyroid glands during bilateral neck exploration for hyperparathyroidism in an experimental setting has been described [6,16]. As an intermediate of heme biosynthesis, ALA is a naturally occurring substance and precursor of fluorescent protoporphyrin IX (PpIX), which can act as a photosensitizer.…”
mentioning
confidence: 99%
“…Fluorescence diagnosis using aminolevulinic acid (ALA) to identify parathyroid glands during bilateral neck exploration for hyperparathyroidism in an experimental setting has been described [6,16]. As an intermediate of heme biosynthesis, ALA is a naturally occurring substance and precursor of fluorescent protoporphyrin IX (PpIX), which can act as a photosensitizer.…”
mentioning
confidence: 99%
“…To our knowledge, only a single group has described the use of 5‐ALA for fluorescent detection of parathyroid tissue. Gahlen et al 18–20 have demonstrated fluorescent visualization of parathyroid glands in normal rats as well as a model simulating secondary hyperparathyroidism in rats genetically engineered to express polycystic kidney disease. In our experiments, significantly higher doses were required to observe parathyroid fluorescence 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Gahlen et al 18–20 have demonstrated fluorescent visualization of parathyroid glands in normal rats as well as a model simulating secondary hyperparathyroidism in rats genetically engineered to express polycystic kidney disease. In our experiments, significantly higher doses were required to observe parathyroid fluorescence 18,19 . Zero animals in our trials had parathyroid tissue fluorescence detected at their published optimal doses of 50 mg/kg at 2 hours and 100 mg/kg at 4 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence‐guided detection of normal parathyroid glands using 5‐aminolevulinic acid (5‐ALA) has been reported recently in rats 7–9. However, there are few reports of fluorescence‐guided localization of normal parathyroid glands in humans.…”
Section: Introductionmentioning
confidence: 99%